Flavonoids in Different Parts of Lysimachia clethroides Duby Extracted by Ionic Liquid: Analysis by HPLC and Antioxidant Activity Assay - Jin-feng Wei; Zhi-juan Zhang; Li-li Cui; Wen-yi Kang (Journal of Chemistry)
To establish methods for simultaneous determination of isoquercitrin, astragalin in leaves, quercetin, and kaempferol in flowers of Lysimachia clethroides Duby, respectively, the methods were ultrasound-assisted extraction combined with RP-HPLC, and ionic liquid was used as the extraction solvent. Meanwhile, the antioxidant activity of the different extracts of L. clethroides was evaluated. Purospher STAR RP-C18 column (4.6 mm × 250 mm, 5 μm) was used for analysis. The flow rate was 0.6 mL·min−1, and the column temperature was 25°C. The detection wavelength was 360 nm. The mobile phases a and b consisted of acetonitrile-0.4% phosphoric acid (18 : 82, v/v), methanol (A), and 0.4% phosphoric acid (B), respectively. Linear ranges were 0.068~1.64, 0.060~1.44, 0.0080~0.19, and 0.0077~0.18 μg for isoquercitrin, astragalin, quercetin, and kaempferol, respectively. The average recoveries of the four constituents were 99.17%, 98.39%, 100.68%, and 98.81%, respectively. The antioxidant activity of the extracts was detected by DPPH, ABTS, and FRAP. Under the optimized conditions, all the test solutions showed a certain antioxidant activity and the ionic liquid extracts were better than that of extract of methanol. Ionic liquid used as the extraction solvent had the potential to extract active ingredients efficiently from L. clethroides, and this method improved the antioxidant activity with accurate and reliable results.